Analisis Pemikiran Hans Küng Tentang Etika Global dan Relevansinya bagi Pendidikan Agama Katolik - Evimawati Harefa; Dominikus Wardoyo; Yessi Florentina Pasaribu; Maria Degli Angeli Fau; Kristiana Liliejeri Lase; Bonifasius Junius Gulo (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This research is motivated by the increasingly complex life of global society, characterized by the intensity of intercultural and interreligious encounters and diverse value systems. These interactions often give rise to conflict, intolerance, and moral crises in social life. Hans Küng's idea of ​​global ethics offers an ethical framework that emphasizes the importance of universal moral values ​​as the basis for peaceful coexistence. This research aims to examine Hans Küng's thoughts on global ethics and examine their relevance for the development of Catholic Religious Education. The method used a qualitative descriptive approach through literature study. Data were obtained from Hans Küng's main works and various scientific literature discussing global ethics, interreligious dialogue, and religious education as secondary sources. Data analysis was carried out through descriptive-analytical stages of data reduction, presentation, and interpretation. The results of the study indicate that the concept of global ethics emphasizes universal moral principles such as respect for human dignity, justice, solidarity, honesty, and shared responsibility. These values ​​encourage constructive interreligious dialogue and cross-cultural cooperation in a pluralistic society. Integrating global ethical principles into Catholic Religious Education helps shape individuals who are moral, tolerant, and open to diversity, moving beyond doctrine toward dialogue and social peace.